2005
DOI: 10.1007/s00239-004-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Full-Length and Deleted Forms of the Mariner-LikeElement, Botmar1, in the Genome of the Bumble Bee, Bombus terrestris (Hymenoptera: Apidae)

Abstract: Mariner-like elements (MLE) are Class II transposable elements that are very widespread among eukaryotic genomes. One MLE belonging to the mauritiana subfamily, named Botmar1, has been identified in the genome of the bumble bee, Bombus terrestris. gDNA hybridization with the Botmar1 transposase ORF revealed that about 230 elements are present in each haploid genome of B. terrestris that consist entirely of 1.3- and 0.85-kbp elements. The analysis of their sequences revealed that there are two Botmar1 subfamili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Red boxes correspond to the predicted bipartite and monopartite NLS, the blue dashed box corresponds to the Helix-Turn-Helix motif of the TIR binding domain, and the yellow box to a motif conserved in mariner elements (Robertson 1993;Bui et al 2007) spiraecola, B. amygdalinus, H. pruni, P. persicae, and T. aurantii) genomes using the inverted terminal repeat of the Mos1 element as primers, whereas the eighth species (A. punicae) was negative. This finding is not surprising, and is in agreement with previous reports showing that MLEs are widespread and diverse in insects (Robertson 1993;Rouleux-Bonnin et al 2005;Wang et al 2011). Other mariner elements belonging to other Subfamilies may exist in these aphid species as reported by Mittapalli et al (2011), which have shown the presence of irritans (Agmar1) and mellifera (Agmar2) elements in the genome of the soybean aphid A. glycine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Red boxes correspond to the predicted bipartite and monopartite NLS, the blue dashed box corresponds to the Helix-Turn-Helix motif of the TIR binding domain, and the yellow box to a motif conserved in mariner elements (Robertson 1993;Bui et al 2007) spiraecola, B. amygdalinus, H. pruni, P. persicae, and T. aurantii) genomes using the inverted terminal repeat of the Mos1 element as primers, whereas the eighth species (A. punicae) was negative. This finding is not surprising, and is in agreement with previous reports showing that MLEs are widespread and diverse in insects (Robertson 1993;Rouleux-Bonnin et al 2005;Wang et al 2011). Other mariner elements belonging to other Subfamilies may exist in these aphid species as reported by Mittapalli et al (2011), which have shown the presence of irritans (Agmar1) and mellifera (Agmar2) elements in the genome of the soybean aphid A. glycine.…”
Section: Discussionsupporting
confidence: 92%
“…This 1,286-bp element, initially designated pch, includes a single open reading frame encoding a protein of 345 amino acids with TIRs of 28 bp at each extremity (Jacobson et al 1986). Since then, numerous mariner elements have been characterized in nematodes (Leroy et al 2003), crustaceans (Casse et al 2006;Bui et al 2007Bui et al , 2008, fish (Ivics et al 1997), human beings (Augé-Gouillou et al 1995;Robertson and Zumpano 1997;Robertson and Martos 1997), plants (Casacuberta et al 1998;Feschotte and Wessler 2002;Zhou et al 2010), protozoans (Silva et al 2005), and insects (Robertson 1993;Robertson and McLeod 1993;Rouleux-Bonnin et al 2005;Wang et al 2011;Rezende-Teixeira et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, these deleted elements could act as inhibitors of trans-mobilization by the full-length copies as described for Botmar1-like copies (Rouleux-Bonnin et al, 2005) or as repressors like the KP deleted form, reported in the P element (Black et al, 1987;Andrews & Gloor, 1995). Furthermore, analysis of the M. destructor genome revealed chimerical elements with 3'-3'extremities that might be generated by either an ectopic recombination replacing 5' extremity by 3' extremity or an internal deletion of an initial head-to-tail mariner close copies as proposed by Filée et al (2015).…”
Section: Discussionmentioning
confidence: 81%
“…We previously reported finding MLEs belonging to the mauritiana sub-family in about 93% of the hymenopteran genomes (Bigot et al, 1994). Recently, we described the isolation and characterization of one of these MLEs, known as Botmar1, in the genome of the bumble bee, Bombus terrestris (Hymenoptera, Apidae; Rouleux-Bonnin et al, 2005). While this species is known to have a very low level of genetic variability (Estoup et al, 1996), the high degree of restriction fragment length polymorphism observed between populations suggests that some Botmar1 members might be active in the genome of this species.…”
Section: Introductionmentioning
confidence: 98%